2013
DOI: 10.1080/13602381.2013.807602
|View full text |Cite
|
Sign up to set email alerts
|

The effect of institutional isomorphic pressure on the internationalization of firms in an emerging economy: evidence from China

Abstract: This study uses institutional theory to explore the driving force for internationalization of firms in emerging economies. It posits that the internationalization practices of firms are driven not only by efficiency consideration, but also by the desire to conform to institutional isomorphic pressures exerted by the social environment. The impact of three types of institutional isomorphic pressures -coercive pressure, mimetic pressure and normative pressure -on the intensity of internationalization is investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 63 publications
3
44
2
Order By: Relevance
“…From this perspective, SMEs having an export business are more likely to gain ISO certification in order to facilitate further integration into the international market through responding to the institutional constraints beyond the domestic market (Boso, Cadogan, & Story, 2012;Kumar, Mudambi, & Gray, 2013;Li & Ding, 2013). Furthermore, the negative side of internationalisation may be exacerbated for emerging country SMEs, which may suffer from more severe latecomer disadvantages and liabilities of foreignness due to a lack of competence and experience in international market (Boso et al, 2012;Zhang et al, 2014).…”
Section: Innovativeness Of Smes and Iso 9000 Certificationmentioning
confidence: 94%
“…From this perspective, SMEs having an export business are more likely to gain ISO certification in order to facilitate further integration into the international market through responding to the institutional constraints beyond the domestic market (Boso, Cadogan, & Story, 2012;Kumar, Mudambi, & Gray, 2013;Li & Ding, 2013). Furthermore, the negative side of internationalisation may be exacerbated for emerging country SMEs, which may suffer from more severe latecomer disadvantages and liabilities of foreignness due to a lack of competence and experience in international market (Boso et al, 2012;Zhang et al, 2014).…”
Section: Innovativeness Of Smes and Iso 9000 Certificationmentioning
confidence: 94%
“…The increasing weight of Chinese firms in the global market can-to a great extent-be attributed to the Chinese government [4,13], which has issued a number of policies and support strategies to promote the "going out strategy," such as providing financial incentives (tax incentives, tax breaks, and low-interest loans) for "going out" firms, encouraging domestic firms to acquire international high-tech firms and establish international branches, and signing national bilateral and multilateral treaties to promote international investment [11]. Therefore, compared with the internationalization of MNCs from developed countries, that of Chinese firms is usually accompanied by government promotion and-to some extent-reflects the government's purpose [10,11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined factors affecting the emergence of Chinese MNEs and have found that Chinese outward FDI is influenced by a variety of firm, industry, and country-related factors (Buckley et al 2007;Li and Ding, 2013;Lu, Liu and Wang 2011;Luo, Xue and Han 2010;Rui and Yip, 2008). The findings from existing studies have shed new light on this issue and enhanced our understanding of the characteristics of Chinese outward FDI.…”
mentioning
confidence: 85%
“…While prior research has examined the impact of home and host country institutions on internationalisation (Guler and Guillén 2010;Li and Ding, 2013;McGahan and Victer 2010;Pangarkar and Lim 2003;Schwens and Kabst 2011;Wan and Hoskisson 2003) and has found that contextual factors play an important role in overseas expansion, this line of research has largely focused on institutions within the boundary of individual countries (Kostova, Roth and Dacin 2008). Several researches have extended this line of research by exploring the role of institutional distance between home and host countries in order to provide a more holistic view (e.g.…”
Section: Literature Backgroundmentioning
confidence: 99%